Study on the physiological responses and tolerance mechanisms to subchronic carbonate alkalinity exposure in the gills of Paramisgurnus dabryanus - Luojia Li; Wei Luo; Pengyu Chen; Yujun Wang; Dan Liu; Yuzhou Lan; Xialin Chen; Lechan Zhou; Shiyong Yang; Zongjun Du (Ecotoxicology and Environmental Safety)
Given the reduction of freshwater resources, saline-alkaline aquaculture has emerged as an effective approach to expand the fishery's accessible space. High carbonate alkalinity (CA) is a major stressor for aquatic organisms in saline-alkaline environments. Paramisgurnus dabryanus is a potential species for culture in saline-alkaline water, making it an ideal model for investigating the physiological responses and tolerance mechanisms to CA exposure in freshwater fishes. In the current study, P. dabryanus were exposed to 15 and 30 mmol/L NaHCO3, combining blood biochemical, gill histological, transcriptomic, and metabolomic methods for conjoint analysis of response mechanisms. After 28-d exposure, the gill ventilation frequency of P. dabryanus decreased significantly, gill lamellae twisted and atrophied, and gill filament epithelial cells proliferated, potentially limiting gas exchange, whereas the accessory air-breathing frequency increased significantly, possibly for greater oxygen uptake. Serum osmolality and blood pH remained relatively steady, while serum ammonia levels rose significantly. A total of 3718 differentially expressed genes (DEGs) and 205 differential metabolites (DMs) were identified between the control group and 30 mmol/L NaHCO3 group, involved in ion transport (Na+/K+-ATPase, V-type ATPase, carbonic anhydrase, and ABC transporters), ammonia transport (Rh glycoproteins and Aquaporins), amino acid metabolism, carbohydrate metabolism, and fatty acid metabolism. Furthermore, DEGs were significantly associated with cell-cell/ extracellular matrix interaction and protein synthesis. An integrated multi-omics analysis revealed the activation of carbon metabolism and TCA cycle. These results indicate that in response to CA exposure, P. dabryanus may facilitate carrier-mediated ion and ammonia transport to maintain the internal osmotic equilibrium and lessen the deleterious effects of blocked ammonia excretion. Meanwhile, amino acid metabolism and protein synthesis are disturbed, P. dabryanus can modulate carbohydrate catabolism to maintain energy homeostasis. The above findings provide novel insights into saline-alkaline adaptation in freshwater fishes, paving the way for future research and development of saline-alkaline-tolerant Cobitidae strains.